2005
DOI: 10.1096/fj.05-4008fje
|View full text |Cite
|
Sign up to set email alerts
|

Dietary soy isoflavone‐induced increases in antioxidant and eNOS gene expression lead to improved endothelial function and reduced blood pressure in vivo

Abstract: Epidemiological evidence suggests that populations consuming large amounts of soy protein have a reduced incidence of coronary heart disease (1–5). The cardiovascular risks associated with conventional hormone replacement therapy in postmenopausal women (5–7) have precipitated a search for alternative estrogen receptor modulators. Here we report that long‐term feeding of rats with a soy protein‐rich (SP) diet during gestation and adult life results in decreased oxidative stress, improved endothelial function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
143
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(150 citation statements)
references
References 59 publications
5
143
0
2
Order By: Relevance
“…23 Cellular defenses against oxidative stress also include superoxide dismutase, catalase, and glutathione peroxidase, all of which are increased with either estrogen or genistein. 11,45,46 In conclusion, the results of this study demonstrate favorable effects of genistein on physical characteristics in the OVX rat, used here as a model for the postmenopausal condition. These favorable effects are evidenced by increased uterine weight and femur weight, along with reduced heart rate and pulse pressure.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…23 Cellular defenses against oxidative stress also include superoxide dismutase, catalase, and glutathione peroxidase, all of which are increased with either estrogen or genistein. 11,45,46 In conclusion, the results of this study demonstrate favorable effects of genistein on physical characteristics in the OVX rat, used here as a model for the postmenopausal condition. These favorable effects are evidenced by increased uterine weight and femur weight, along with reduced heart rate and pulse pressure.…”
supporting
confidence: 58%
“…8 One of the more notable cardiovascular-related effects of genistein is a lowering of blood pressure observed in both hypertensive and normotensive postmenopausal women 9,10 or rat models. 11 This beneficial effect is purported to be mediated via improvements in endothelial function and reductions in both antioxidant stress in aorta and arterial stiffness. 12 Moreover, genistein treatment in postmenopausal women was shown to increase flow-mediated endothelium vasodilation, likely by increasing the nitric oxide to endothelin ratio, 11,[13][14][15] and has a beneficial effect on the lipid profile.…”
Section: Introduction Lmentioning
confidence: 99%
See 2 more Smart Citations
“…The U.S. Food and Drug Administration has endorsed the benefits of soy-based food products in lowering arterial blood pressure and oxidative stress in human subjects with mild to moderate hypertension (Hodgson et al, 1999;Rivas et al, 2002). In addition, a recent report showed that dietary soy protein leads to increased antioxidant, endothelial nitric oxide synthase gene expression and protected cancers, resulting in improved endothelial function in vitro, and reduced blood pressure in vivo in aging male rats (Mahn et al, 2005). Chinese traditional medicine has become increasingly popular and widely used over recent years.…”
Section: Discussionmentioning
confidence: 99%